"Written on My Heart in Burning Letters": Putting Soul and Spirit Into a Transcendent Physis. (3rd April 2019) - Milnes, Peter
Abstract: The author suggests that one way to help transactional analysts to better understand spirituality and the way it relates to religiosity and psychopathology is to view them in terms of the core TA concept of physis and, specifically, as a fiery physis that transcends scripting. He distinguishes between the often interchangeable terms of faith, religion, and spirituality and, using TA literature, locates the genesis of the religious terms of soul and spirit more firmly within the ego state model. He further shows how numinous feelings begun in the Child ego state continue throughout life and proposes that a fiery physis can be illustrated through the analysis of the Leonard Cohen song "Born in Chains, " in which the metaphor of "burning" described his spiritual experience. The author also describes the widely publicized return to faith of the Hon. William Hayden, a former governor general of Australia. The proposal is made that an emotionally based spirituality referred to as fiery physis is formed in infancy and continues throughout life because religious faith and spirituality are more immediate and helpful in difficult circumstances than an intellectual faith. The author proposes that a clear understanding of religious faith and spirituality can enrich transactional analysis.